Determining Hazard Area - Wijatmiko, Indradi (Jurnal Mahasiswa Jurusan Teknik Sipil, 2014)
It has been known that Kyushu island is valnurable against tsunami, therefore several strategies need to be cleared in order to protect against casualities.